Faunal exploitation during the Proto-Zhou period in the Jing River Valley: Evidence from Sunjia and Xitou - Festa, Marcella; Dou, Haifeng; Monteith, Francesca; Orton, David; Wang, Qianwen; Zong, Tianyu; Liu, Bin; Li, Yue (Frontiers in Earth Science, 2023)
This study examines faunal assemblages from the Proto-Zhou sites of Sunjia and Xitou, in the Jing River Valley (Central Shaanxi Province), to address questions concerning the exploitation of different animal resources in the context of the Shang-Zhou dynastic transition in the 11th century BCE. Although the assemblages from Sunjia and Xitou were small and sub-optimally preserved, this study demonstrates that the inclusion of such assemblages is essential to building upon our understanding of the human exploitation of animal resources. Our zooarchaeological analysis shows an increase in husbandry, with pig farming being complemented by extensive caprine and cattle herding. A diversified use of animal resources, and especially the larger number of bovids, could have been prompted by the need for a wider and more efficient exploitation of the immediate environment, in response to growing climatic deterioration, in addition to an increase in interactions with northern pastoral communities. Identified patterns of livestock biometry and relative taxonomic abundance show various degrees of agricultural engagement and a relatively complex livestock economy, suggesting the development of socio-economic complexity in the Jing River Valley in the late second millennium BCE.